Pitfalls of Research Linking the Intrauterine Device to Pelvic Inflammatory Disease - Hubacher, David; Grimes, David A.; Gemzell-Danielsson, Kristina (Obstetrics and gynecology (New York. 1953), 2013)
Correctly diagnosing pelvic inflammatory disease (PID) using noninvasive clinical criteria remains challenging. Current guidelines for initiating treatment, based on minimal criteria (sensitive but not specific), are justified for public health purposes but inadequate and misleading for scientific purposes. Previous research on the link between the intrauterine device (IUD) and PID was controversial and subject to many limitations. Even today, these limitations still exist and include uncertainty of the PID diagnosis, unfair contraceptive comparisons, selection and diagnostic bias, and confounding. For example, IUD users are on heightened alert for PID relative to users of other methods. In addition, IUD users with pelvic pain may be more likely to seek physician consultation and consequently receive a PID diagnosis (true-positive or false-positive). Confounding factors such as higher coital frequency, multiple sexual partners, and low condom use may explain any finding that shows a higher PID rate among IUD users compared with other contraceptive users. Good evidence on how or whether the IUD changes the etiology of PID is lacking. In the past 10 years, use of the intrauterine device in the United States has increased markedly. Thus today, researchers may now have sufficient population-level exposure (IUD use) and disease (PID) to search for a connection and repeat past mistakes. Any new findings using observational research should be interpreted with caution. More rigorous research designs may not be pragmatic or feasible.